CIRDES - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
In 1994 the Centre for Research on Animal Trypanosomiasis, which was established in 1972, was renamed the International Centre for Research and Development of Livestock in the subhumid zone (CIRDES). CIRDES, which has a regional mandate, has its...